2021
DOI: 10.1101/2021.02.01.429258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct neurophysiological correlates of the fMRI BOLD signal in the hippocampus and neocortex

Abstract: Functional magnetic resonance imaging (fMRI) is among the foremost methods for mapping human brain function but provides only an indirect measure of underlying neural activity. Recent findings suggest that the neurophysiological correlates of the fMRI blood-oxygen-level-dependent (BOLD) signal might be regionally specific. We examined the neurophysiological correlates of the fMRI BOLD signal in the hippocampus and neocortex, where differences in neural architecture might result in a different relationship betw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…no hippocampal activity has been shown in fMRI in this (Figure 2c) or previous odd-ball-paradigm fMRI studies [Kim, 2014]. One possible reason for this negative finding could be different neurovascular coupling in medial temporal lobe compared to neocortex [Hill et al, 2021], suggested recently based on combined iEEG and fMRI. While the contribution of a hippocampal source to the parietal P3 in EEG had already been excluded based on lesion studies [Johnson, 1988;Onofrj et al, 1992], this does not exclude that hippocampal activity may generally contribute to other aspects of the M/EEG response [Alberto et al, 2021], even though with only a weak signal-to-noise ratio.…”
supporting
confidence: 40%
“…no hippocampal activity has been shown in fMRI in this (Figure 2c) or previous odd-ball-paradigm fMRI studies [Kim, 2014]. One possible reason for this negative finding could be different neurovascular coupling in medial temporal lobe compared to neocortex [Hill et al, 2021], suggested recently based on combined iEEG and fMRI. While the contribution of a hippocampal source to the parietal P3 in EEG had already been excluded based on lesion studies [Johnson, 1988;Onofrj et al, 1992], this does not exclude that hippocampal activity may generally contribute to other aspects of the M/EEG response [Alberto et al, 2021], even though with only a weak signal-to-noise ratio.…”
supporting
confidence: 40%
“…Furthermore, in the case of simultaneous EEG/fMRI, the temporal information available from EEG can be used to supplement and better understand the co-occurring fMRI signal (Chang and Chen, 2021; Murta et al, 2015) or potentially confirm novel hemodynamic findings (Lewis et al, 2016). Studies combining EEG and fMRI have spanned the full range experimental paradigms routinely used in fMRI, from naturalistic stimuli (Whittingstall et al, 2010), to resting state (Deligianni et al, 2014; Goldman et al, 2002; Mayhew and Bagshaw, 2017; Meyer et al, 2013; Wirsich et al, 2020) and typical task based approaches (Hill et al, 2021; Mayhew and Bagshaw, 2017).…”
Section: Statistical and Methodological Considerationsmentioning
confidence: 99%